Avaliação da resposta biológica inflamatória e capacidade de biomineralização de cimentos endodônticos resinosos obturadores - Sobral, Luana Bastos [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
The obturation of the root canal system aims to fill empty spaces previously occupied by the root pulp, aiming for a hermetic seal and providing conditions for repair and biological sealing through the biomineralization process. Therefore, characteristics such as biocompatibility and inducing the deposition of mineralized tissue (biomineralization) are fundamental for obturation cements, since they will be in direct contact with periapical tissues. This study evaluated the inflammatory response and mineralization induction of 3 resin-based endodontic obturation cements. Twenty Wistar rats were used, receiving 3 subcutaneous implants of polyethylene tubes containing Endosealer, Endosealer Plus, and Endosealer Premium cements, and an empty tube as a control (n=10 animals/group). After 7 and 30 days, the animals were euthanized, and the polyethylene tubes were removed along with the adjacent tissues. Inflammatory infiltrate and fibrous capsule thickness were histologically evaluated by assigning inflammatory scores (scores 0, 1, 2, and 3) according to the intensity of the inflammation. The presence of mineralized tissue was assessed by Von Kossa staining and without staining for analysis of birefringent crystals under polarized light. In the initial periods, all groups showed inflammation score 2 with a thick fibrous capsule that regressed after 30 days, surrounded by a thin fibrous capsule. Von Kossa staining and polarized light were negative for all groups in both experimental periods. The resin obturation sealers tested were biocompatible but did not induce biomineralization.

The obturation of the root canal system aims to fill empty spaces previously occupied by the root pulp, aiming for a hermetic seal and providing conditions for repair and biological sealing through the biomineralization process. Therefore, characteristics such as biocompatibility and inducing the deposition of mineralized tissue (biomineralization) are fundamental for obturation cements, since they will be in direct contact with periapical tissues. This study evaluated the inflammatory response and mineralization induction of 3 resin-based endodontic obturation cements. Twenty Wistar rats were used, receiving 3 subcutaneous implants of polyethylene tubes containing Endosealer, Endosealer Plus, and Endosealer Premium cements, and an empty tube as a control (n=10 animals/group). After 7 and 30 days, the animals were euthanized, and the polyethylene tubes were removed along with the adjacent tissues. Inflammatory infiltrate and fibrous capsule thickness were histologically evaluated by assigning inflammatory scores (scores 0, 1, 2, and 3) according to the intensity of the inflammation. The presence of mineralized tissue was assessed by Von Kossa staining and without staining for analysis of birefringent crystals under polarized light. In the initial periods, all groups showed inflammation score 2 with a thick fibrous capsule that regressed after 30 days, surrounded by a thin fibrous capsule. Von Kossa staining and polarized light were negative for all groups in both experimental periods. The resin obturation sealers tested were biocompatible but did not induce biomineralization.
Evaluation of the inflammatory biological response and biomineralization capacity of resin-based endodontic sealers
Keywords: Biomineralização; Endodontia; Inflamação; Restaurações (Odontologia); Endodontics